Negative outcomes in attention-deficit/hyperactivity disorder comorbid with oppositional defiant disorder - ERDOĞDU, AYŞE BURCU (Cambridge University Press, 2014)
Objectives. In children and adolescents diagnosed with attention-deficit/hyperactivity disorder (ADHD), the comorbidity of the oppositional defiant disorder (ODD) negatively affects the course of ADHD. The purpose of this study was to compare ADHD-diagnosed children with and without ODD comorbidity in terms of smoking, psychoactive substance use, disciplinary punishments at school, criminal behaviors, and unintentional injuries. Methods. This study included 109 children diagnosed with ADHD alone and 79 children with the ADHD-ODD comorbidity from a child psychiatry outpatient clinic. The children who participated in the study were aged between 6 and 15 years. Diagnoses of the children were determined by child psychiatrists according to DSM-IV criteria, and the Turgay DSM-IV-based Child and Adolescent Behavior Disorders Screening and Rating Scale-Parents Form was used to support the diagnosis in initial evaluations of children. Forty-six to fifty months after the first admission, parents were questioned regarding all negative outcomes from the time of first diagnosis to the time of the evaluation by phone. Results. The groups were compared in terms of smoking, psychoactive substance use, disciplinary punishments at school, criminal behaviors, and unintentional injuries over a period of 4 years. The ODD-ADHD group was determined to have higher rates of disciplinary punishments at school, smoking, and unintentional injuries compared with the ADHD group. No statistically significant difference was found between the two groups in terms of criminal behaviors and psychoactive substance use. Conclusions. The ODD comorbidity increases the risk of negative outcomes in children diagnosed with ADHD. © College of Psychiatrists of Ireland 2015.
Keywords: Attention-deficit/hyperactivity disorder; Children; Comorbidity; Negative outcome; Oppositional defiant disorder